Henryk Sienkiewicz i poezja – krytyka, praktyka - Klimek-Grądzka, Jolanta (Acta Universitatis Lodziensis. Folia Linguistica, 2016)
Subject to analysis in this article are the poetic and the metapoetic statements made by Henryk Sienkiewicz. Even though the latter category is now and then analysed in lingustic research – as part of the analyses of Sienkiewicz’s legacy as a columnist and a reviewer – the former category remains terra incognita for language researchers. The first part of the article analyses the key concepts of Sienkiewicz’s metapoetic statements (e.g. talent [gift, talent] or prostota [simplicity]) as well as the stylistic qualities of these statements (e.g. poetic nature, emotionality). The second part of the article features a linguistic analysis of the idiostylistic qualities of Sienkiewicz’s poetic works: grammar of rhymes, selection of stylistic means (e.g. parallels and epithets) as well as his choice of the lexical stock.